Calculation of the Risk Index for Diarrhea, ISPA, and Pneumonia in Toddlers in the City of Bandung Using Geographically Weighted Principal Component Analysis - Azka Larissa Rahayu; Gumgum Darmawan; I Gede Nyoman Mindra Jaya (PT FORMOSA CENDEKIA GLOBAL, 2023)
Diarrhea, ISPA, and pneumonia are infectious diseases that are prone to occur in toddlers. The management of these three diseases is included in the Republic of Indonesia Ministry of Health's National Priorities for 2020-2024. One area that has a high risk of diarrhea, ARI, and pneumonia in toddlers is the city of Bandung. Effective and efficient disease control is needed, namely by controlling the three diseases simultaneously which can be emphasized on improving environmental quality, especially in areas with high disease risk. The analysis found that there is a spatial dependence on each variable and each variable is correlated with one another. Therefore, in this study used Geographically Weighted Principal Component Analysis (GWPCA). Calculation of the risk index and mapping with GWPCA produces a combined risk index of the three observed diseases by considering the spatial dependence of the data.